Petites exploitations laitières au Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
La production laitière se répartit, au Zimbabwe, en deux segments très contrastés. Les producteurs commerciaux,